2022
DOI: 10.3390/ijms232113252
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of RNA-seq Data Reveals Genes Related to Cancer Stem Cells in Colorectal Cancerogenesis

Abstract: Cancer stem cells (CSC) play one of the crucial roles in the pathogenesis of various cancers, including colorectal cancer (CRC). Although great efforts have been made regarding our understanding of the cancerogenesis of CRC, CSC involvement in CRC development is still poorly understood. Using bioinformatics and RNA-seq data of normal mucosa, colorectal adenoma, and carcinoma (n = 106) from GEO and TCGA, we identified candidate CSC genes and analyzed pathway enrichment analysis (PEI) and protein–protein interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 103 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…The top 10 hub genes in CRC in the PPI network interaction map were CDK1, CCNA2, CCNB1, CDC20, BUB1B, BUB1, DLGAP5, CCNB2, KIF11, and KIF20A. CDK1 is signi cantly differentially expressed in CRC with lymph node metastasis compared with that in normal mucosa [25] . CCNB1 is associated with survival in stage II CRC [26] .…”
Section: Discussionmentioning
confidence: 98%
“…The top 10 hub genes in CRC in the PPI network interaction map were CDK1, CCNA2, CCNB1, CDC20, BUB1B, BUB1, DLGAP5, CCNB2, KIF11, and KIF20A. CDK1 is signi cantly differentially expressed in CRC with lymph node metastasis compared with that in normal mucosa [25] . CCNB1 is associated with survival in stage II CRC [26] .…”
Section: Discussionmentioning
confidence: 98%
“…Conventionally, clinicians often depend on clinical characteristics, such as age, sex and TNM stage, to predict the survival of cancer patients and guide the treatment 14 . With the advent of high‐throughput sequencing and bioinformatics, people can draw on the transcriptome data and find the critical genes tightly associated with the patient survival, and constructed prognostic models to evaluate cancer prognosis more accurately 15 . In this study, we established a riskscore model in light of Treg‐associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…14 With the advent of high-throughput sequencing and bioinformatics, people can draw on the transcriptome data and find the critical genes tightly associated with the patient survival, and constructed prognostic models to evaluate cancer prognosis more accurately. 15 In this study, we established a riskscore model in light of Treg-associated genes. The riskscore of each patient can be calculated from the expression value of seven key genes.…”
Section: Association Of Key Gene Expression With Treg Infiltrationmentioning
confidence: 99%
“…In our study, the population size was set to 10 individuals, the maximum number of evolutions was 1,000, the roulette wheel method was used as the selection operator, and the crossover rate and variation rate were both 0.1. The fitness function was particularly important here, and the fitness function cannot be obtained directly in this task formula, which consists of two parts; the first part is calculated from the value of the predicted drug treatment effect by the deep learning model, and the other part is calculated from the number of drug species, and its specific formula is shown in Equation (11), where N denotes the number of best drug species in the combination.…”
Section: Genetic Algorithm Modulementioning
confidence: 99%
“…Jiang et al ( 10 ) found that CDNK3 was the key gene in the progression of cirrhosis to hepatocellular carcinoma. In addition, Urh et al ( 11 ) bioinformatically analyzed normal mucosal, colorectal adenoma, and colorectal cancer differential genes from GEO as well as The Cancer Genome Atlas (TCGA) databases and found that tumor stem cell-related genes (ANLN, CDK1, ECT2, and TNC) were associated with colorectal carcinogenesis, while ANLN and PDGFD genes were associated with the progression of colorectal cancer, but the mechanism of action of these genes with the development of colorectal cancer still needs further study and validation.…”
Section: Introductionmentioning
confidence: 99%